Management of intangible assets of relational capital in Higher Education Institutions (2019)
Knowledge Management (CG) in Higher Education Institutions (HEI) can be analyzed through the identification of intangible assets. These assets are able to generate competitive advantage. One of these assets is Relational Capital (RC). RC involves interaction with different stakeholders, knowledge acquisition and knowledge transfer. The aim of this study is to characterize the interaction between relational capital categories in HEI. A case study methodology was used. Linear bivariate Pearson correlation and the proportion of shared variability were used. Among the main results, it was identified that strategic management was one of the main drivers that allow HEI to generate relevant characteristics. Strategic management also increases the level of institutional identity of the teachers linked to research groups. Likewise, quality teaching profile facilitates the establishment of trust relationships and the satisfaction of the requirements of different institutional stakeholders.